Enhancing academic mindfulness through shaping-based time management: Evidence from a quasi-experimental study - Tamami, Abi Syamsudin; Azizah, Luthfiya Zulfatul; Jamaluddin, Muhammad (Journal of Indonesian Psychological Science (JIPS), 2025)
College students often experience academic pressure stemming from performance demands, study load, and organizational activities, which can trigger stress and reduce academic mindfulness—the ability to be fully present during the learning process. Such pressure also hinders effective time management, thereby increasing mind-wandering and decreasing cognitive engagement. This study aimed to examine the effect of a shaping-based intervention targeting effective time management behaviors on the enhancement of academic mindfulness. The research employed a pre-test–post-test nonequivalent control group design involving 20 participants, consisting of 10 in the control group and 10 in the experimental group. The intervention was conducted in three sessions using shaping techniques through time blocking, self-reflection, and priority setting. Academic mindfulness was measured using an adapted version of the Mindfulness Attention Awareness Scale (MAAS) for the academic context. The results indicated a significant improvement in the experimental group compared to the control group (p = 0.009 0.05). These findings suggest that the shaping-based intervention effectively enhances academic mindfulness and has the potential to expand experimental psychology research as well as contribute to the development of campus-based psychological interventions aimed at improving students’ academic well-being KEY WORDS: time management; academic mindfulness; students; shaping; time blocking; behavior modification